Pelatihan inovasi produk olahan jamur tiram di desa Solokuro kabupaten Lamongan - Fais Wahidatul Arifatin; Farid Effendi; Diana Novita Sari; Adelia Asti Septiana (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2021)
In today's era, innovation in any case is a demand. No exception innovating in a processed product. Solokuro village is one of the villages in Lamongan district. Oyster mushroom itself is not a new food ingredient for local residents. Although most of them are rice and corn farmers, some are farming oyster mushrooms. One of them is Jaya Mulia Solokuro (JMS) as one of the SMEs in Solokuro village that cultivates oyster mushrooms, and has partners in the cultivation and marketing of oyster mushrooms themselves. JMS only sells oyster mushrooms to traders, shop owners or other partners. Although sometimes the harvest of oyster mushrooms is abundant, the farmers only focus on selling mushrooms. With limited insight in the processing of oyster mushrooms, the team of writers motivated to do community service through this training. This training was attended by 62 residents on 27 August 2021 at the Solokuro village hall. The purpose of this training is to provide insight and explore the potential of the surrounding community to be more innovative, especially in terms of processing oyster mushrooms. From the results of the study, it is showed that the Solokuro village community can increase their creativity in entrepreneurship.